Oray-Orayan dalam Perspektif Struktural: Menelisik Tradisi Lisan dan Kearifan Lokal Kota Cimahi - Ayu Widiyani Sigid; Yulianeta; Tedi Permadi; Khairul Fuad (Tambo: Journal of Manuscript and Oral Tradition, 2026)
This study was motivated by the decline of traditional games in urban areas, which has hindered the process of cultural value inheritance. The study focused on the narratives found in the children's game "Oray-orayan" played by children in three areas in the Cimahi Tengah sub-district, Cimahi City. Data was collected through observation, documentation, and transcription of the game songs. The study employed a qualitative method with Claude Lévi-Strauss's structural approach. The analysis revealed that the game songs contain a narrative structure that incorporates ethical values, social norms, and cultural symbols of an agrarian society. Binary oppositions such as sawah (rice field) versus leuwi (deep river) and entong (don't) versus mending (rather than) reflect symbolic conflicts that construct cultural meaning within the game song. These findings affirm that traditional games like Oray-orayan serve an important function as a medium for transmitting local wisdom while also functioning as an educational tool in shaping children's character.